Quantifying volume loss from ice cliffs on debris-covered glaciers using high resolution terrestrial and aerial photogrammetry - Brun, Fanny; Buri, Pascal; id_orcid:0 000-0003-3890-2109; Miles, Evan S.; Wagnon, Patrick; Steiner, Jakob; Berthier, Etienne; Ragettli, Silvan; Kraaijenbrink, Philip; Immerzeel, Walter W.; Pellicciotti, Francesca (International Glaciological Society, 2016)
Mass losses originating from supraglacial ice cliffs at the lower tongues of debris-covered glaciers are a potentially large component of the mass balance, but have rarely been quantified. In this study, we develop a method to estimate ice cliff volume losses based on high-resolution topographic data derived from terrestrial and aerial photogrammetry. We apply our method to six cliffs monitored in May and October 2013 and 2014 using four different topographic datasets collected over the debris-covered Lirung Glacier of the Nepalese Himalayas. During the monsoon, the cliff mean backwasting rate was relatively consistent in 2013 (3.8 ± 0.3 cm w.e. d−1) and more heterogeneous among cliffs in 2014 (3.1 ± 0.7 cm w.e. d−1), and the geometric variations between cliffs are larger. Their mean backwasting rate is significantly lower in winter (October 2013–May 2014), at 1.0 ± 0.3 cm w.e. d−1. These results are consistent with estimates of cliff ablation from an energy-balance model developed in a previous study. The ice cliffs lose mass at rates six times higher than estimates of glacier-wide melt under debris, which seems to confirm that ice cliffs provide a large contribution to total glacier melt. ISSN:0022-1430 ISSN:1727-5652